ORTHOBIOSIS BY ZDRAVOMYSLOV: THE CAREER AND BIOGRAPHICAL MILESTONES OF THE OUTSTANDING SCIENTIST, DOCTOR AND PUBLIC FIGURE VLADIMIR MIKHAILOVICH ZDRAVOMYSLOV (1869-1944) - Nechaev, M.G. (Perm Federal Research Centre Journal, 2016)
In the paper some unknown facts of local virological science of the development are revealed with the help of new materials, concerning the founder of the Perm Bacteriological Institute and the Perm School of Microbiology V.M. Zdravomyslov, an outstanding scientist and doctor. The political situation has not allowed until now to disclose the innovative contribution of V.M. Zdravomyslov to the practice and theory of Microbiology, as well as to reconstruct a complete and reliable picture of his exciting scientific and political life.